Achievement Motivation and Mediating Effect of Preventive Discipline on Task Performance - Silvia Shopiana Haryanti; Aan Hardiyana (P3M, STIE Pasundan, Bandung, Indonesia., 2023)
This study aims to determine the influence of achievement motivation and the mediating role of preventive discipline on task performance. The research method employed a quantitative approach with path analysis using the Structural Equation Modeling (PLS-SEM) technique. The respondents consisted of 31 employees working in a government department in Bandung. The calculation results reveal the mediating role of preventive discipline on task performance, indicating that employees with high achievement motivation, driven by preventive discipline, can enhance task performance. To improve task performance, organizations must establish and reinforce preventive measures in the workplace while actively promoting and supporting employee achievement motivation. This condition can be achieved through goal-setting, implementing recognition programs, and providing opportunities for personal and professional growth. By establishing preventive measures, organizations can create a conducive environment that encourages employees to adhere to guidelines and procedures, preventing potential issues that may hinder task performance. Additionally, actively fostering employees' achievement motivation through goal-setting initiatives and recognition programs can enhance their drive to excel in their tasks. Providing opportunities for personal and professional growth further supports employees' continuous improvement and development. In conclusion, this study highlights the importance of preventive discipline as a mediating factor in the relationship between achievement motivation and task performance. Organizations can enhance task performance by establishing preventive measures, promoting achievement motivation, and supporting employees' personal and professional growth.